Analisis Peran Bahasa Indonesia Terhadap Kejelasan dan Ketepatan Laporan Praktikum Teknik Sipil Mahasiswa Universitas Negeri Medan - Anggi Rona BR Kaban; Dianita Sahda; Fathir Ihsan; Fidelis Simbolon; Hironius Asyer Keith Aritonang; Lasro Dearma Br Simbolon; Hendra Kurniawan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the impact of using the Indonesian language on the clarity and accuracy of preparing practical work reports by students of the Civil Engineering Study Program at Universitas Negeri Medan. The main issue addressed is the low linguistic quality in practical reports, which potentially reduces reader comprehension in terms of sentence structure, word choice, and paragraph organization. The purpose of this research is to identify the extent to which the application of proper and correct Indonesian language principles affects readability, accuracy in conveying information, and the alignment of reports with academic standards in the field of civil engineering. The research employed a qualitative-descriptive approach by analyzing the content of 30 practical work reports written by students. The research instruments included language analysis guidelines and assessment criteria referring to the Indonesian Spelling System (Ejaan Bahasa Indonesia/EBI) and the framework of scientific writing. Data were analyzed through the stages of coding linguistic errors, evaluating content clarity, and assessing technical compliance. The findings affirm that adequate mastery of the Indonesian language is not merely a formality, but rather an essential element in scientific communication within the civil engineering sector.